Nutrition and Dehydration: Players Should Learn How to Bring Them to Life: Nutrition and dehydration - Köse, Gizem; Şam, Cemil Tuğrulhan; Mızrak, Orcan; Acar, Hakan; Tutkun, Erkut (Progress in Nutrition, 2021)
Objective: In the present study, it is aimed to investigate the relationship between nutritional knowledge, hydration, food frequency with their gender and body mass index among students from sports department.Methods: This cross-sectional study was conducted 127 randomly selected undergraduate students in Spring 2019. Participants completed sociodemographic form, and Nutrition Knowledge Level Survey for Adults (NKLSA) questionnaires that included questions related to their eating habits, nutritional knowledge etc. Body weight and height of participants were measured.Results: In the present study, 66.1% of the participants were female and 33.9% were male, the mean age was 20.5±4.15 years; mean body mass index (BMI, kg/m²) was 21.49±2.13; 22.35±2.35 in males and 21.06±1.87 in females (p